PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN MENGGUNAKAN METODE PETA PIKIRAN BAGI ANAK USIA DINI - Ayi Teiri Nurtiani (Visipena, 2013)
The aims of this research are to know the upgrading of learning outcome in islamic study by use of mind map method and are there any increase of grade first class elementary student capability of learning outcome in islamic study after giving the learning outcome in islamic study by use of mind map method. 24 students of first class at Amaliah Elementary Ciawi-Bogor are the subject of this research.This research used action research method according to Kemmis and Mc.Taggart that consist of four step: 1) plan, 2) action, 3) observation, and 4) reflection. The data was collected by filed notes, interview, observation, test, an documentation. The data was analyzed by qualitative and quantitative method.The result of research shows that the learning outcome in islamic study by use of mind map method could increase capability of first class elementary students. Whereas the learning outcome in islamic study consist of cognitive, afective, and psikomotor.